Analysis Of Factors Influencing Smoking Behavior In Adolescents - Sipra Barutu (Journal Health of Indonesian, 2023)
Smoking habits in adolescents is a serious problem with significant health impacts. Serious diseases such as cancer, heart disease and chronic respiratory problems are the consequences of this smoking habit. Adolescents are vulnerable to social pressure, environmental influences, and psychological factors that make it difficult for them to stop smoking. This study analyzes environmental, social, psychological and genetic factors that influence smoking behavior in adolescents through literature studies. These factors include the availability of cigarettes around teenagers, peer influence, stress, and genetic factors. These findings indicate the need for a holistic approach in preventing smoking in adolescents. Policies that limit youth access to cigarettes, changing social norms that support smoking, improving youth emotion management skills, and personalizing interventions based on genetic factors are important steps that must be taken to protect young people from the dangers of smoking. This comprehensive approach is expected to reduce the prevalence of smoking in adolescents, support the growth of a healthier generation, and reduce the negative impact of smoking on society as a whole.